The Palawan Formative Research Project: Context, Methodology and General Findings - Abregana, Betty C. (Silliman Journal, 2023)
PALAWAN, a frontier island province, is part of the Southern Tagalog Region. The province has 22 municipalities and 420 barangays spread in a land area of 14,896.3 sq km. As of 1990, the population was 528,287. The terrain of the province is rugged, particularly on the western portion where a chain of mountain ranges rises to heights up to 2,086 m. Except for the wide plain in the north and pockets of big valleys and delta lands along the shore down to the south, the west coast is practically devoid of coastal land and consists mainly of craggy foothills and mountains close to the sea. Rivers and streams traverse through the province but the most unusual is the seven kilometer underground river flowing under limestone rocks and emptying into Saint Paul Bay. The principal river in the province is Iwahig River (National Statistics Office: Provincial Profile 1990).